Integrating Cyber Ethics into Modern Education to Combat Cybercrime - Afandi, Muhammad Ruslan (Cognitive Insight in Education, 2025)
The rapid advancement of digital technology in education has resulted in a rise in cybercrime incidents impacting students and university attendees, including cyberbullying, digital fraud, and data exploitation. Data shows that approximately 35% of students have experienced cyberbullying, 28% have been victims of digital fraud, and cases of personal data misuse among students have increased significantly in the last five years. This study aims to evaluate the effectiveness of integrating cyber ethics into modern education as a strategy to reduce cybercrime. This study employs a qualitative methodology using a case study framework. The data gathering method employed a systematic literature review (SLR) of the curriculum, pedagogical approaches, and policies related to digital ethics and cybercrime, ensuring the acquired data is comprehensive and credible. The collected data was analyzed using thematic analysis techniques, including data search, identification, categorization, and conclusion drawing. The research findings suggest that incorporating cyber ethics into the digital literacy curriculum, promoting ethical conduct, utilizing case-based learning, and offering teacher training will enhance students' awareness, understanding, and abilities in navigating cyber threats. The implementation of this program underscores the importance of collaboration among schools, parents, higher education institutions, and alignment with government policy on cybersecurity. Incorporating cyber ethics into contemporary education is essential for cultivating a discerning, intelligent, and secure generation capable of engaging in the digital realm.